Fast Impedance Spectroscopy of Piezosensors for Structural Health Monitoring - Märtens, O.; Saar, T.; Min, M.; Land, R.; Reidla, M. (Elektronika ir Elektrotechnika, 2010)
Electroimpedance spectroscopy (EIS) of piezoelectric transducers (PZT) is used in structural health monitoring (SHM) of composites and for checking quality of PZT and bondings. Measurements have to be precise, as small changes in real or imaginary parts of the impedance can indicate early changes in the structure or in the sensor. EIS methods, by one frequency at a time, are time and energy consuming, limiting such approach for embedded systems. Alternative faster methods of EIS are suggested here and tested in an PC-based experimental setup, with a composite plate and PZTs. Usage of simultaneous multi-frequency or wide-band excitation signals like chirps have been studied and compared.